2010
DOI: 10.1002/maco.200905308
|View full text |Cite
|
Sign up to set email alerts
|

Role of second phase particles in pitting corrosion of 3003 Al alloy in NaCl solution

Abstract: The second phase particles in 3003 aluminum (Al) alloy were characterized by scanning electron microscope, energy-dispersive X-ray analysis and X-ray diffraction techniques. The role of second phase particles in Al alloy pitting corrosion was investigated by cyclic polarization measurement, and scanning vibrating electrode technique. Results demonstrated that the second phase particles in 3003 Al alloy are mainly Al x (Fe,Mn) intermetallics, with an average diameter of about 5 mm. The enrichment of Mn in secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…4) are primarily Al x (Fe, Mn) intermetallics, as characterized by previous study [8] as well as the high content of Mn in EDX results in Fig. 5 and Table 2.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…4) are primarily Al x (Fe, Mn) intermetallics, as characterized by previous study [8] as well as the high content of Mn in EDX results in Fig. 5 and Table 2.…”
Section: Discussionmentioning
confidence: 73%
“…5 and Table 2. It has been acknowledged [8,26,27] that the Mn-enriched second phase particles forms a galvanic effect relative to the adjacent Al alloy substrate, where the particles serve as cathode and the Al alloy substrate as anode. Cathodic reactions occurring at second phase particles are dominated by the reduction of oxygen:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous work [36], it was established that a galvanic effect exists between the Mn-enriched second phase particles and the adjacent Al alloy substrate, where second phase particles serve as the cathode and Al alloy as the anode. Occurrence of pitting corrosion of Al alloy is resulted from the local dissolution of the Al alloy substrate around the second phase particles.…”
Section: Pitting Corrosion Of Aa3003 In Ethylene Glycol-water Solutionsmentioning
confidence: 99%
“…Many studies have reported that the corrosion behavior of alloys depends on the second phase distribution, shown to be Mg alloy [61,62] and Al alloy [63]. In the Sn3.5Ag0.Cu nanocomposite solder alloys, the microstructure had finer β-Sn grains, a large amount of Ag 3 Sn particles, and a small amount of oxidize nanoparticles.…”
Section: Corrosion Behavior Of Pb-free Nano-composite Solder Jointsmentioning
confidence: 99%